Plakat "Jakob Baur // wieder in den Ständerat SVP"
politischer Rahmen;Wahlen und Abstimmungen;Wahl;Wahlorganisation;Wahlkampf politischer Rahmen;politische Partei (allgemein);politische Partei (speziell);SVP politischer Rahmen;Wahlen und Abstimmungen;Wahl;Lokalwahl politischer Rahmen;Wahlen und Abstimmungen;Wahl;Wahl der Exekutive